Desenvolvimento de produto educacional para ensino de circuitos elétricos nos anos iniciais do ensino fundamental - Almeida, Gustavo Henrique de (2022)
This research proposes the creation of a didactic material for teaching electrical circuits, as well as its usability assessment. The proposed material was developed using concepts of creation and product designer, resulting in a circuit teaching kit, consisting of a book, electronic components and activity boxes that present the practical exercises in a playful way — as well as bring the illustration of the application of each component. The work also presents the development of the method of product evaluation, elaborated so that it can be used by elementary school students I. Finally, the evaluation of its usability and the results of the application of the material are demonstrated, obtained with the application of a workshop for 57 5th grade students of a public school located in the city of Foz do Iguaçu, Paraná, Brazil. Some of the contribution for the community present in the work are: the description of how to develop didactic material for teaching electric circuits, which can be used for the development of materials for other courses, and the method of evaluation for such materials, which considers the parameters related to the usability of the material from the perspective of the students.